PENGARUH PENGGUNAAN MEDIA FLASH CARD TERHADAP PENGETAHUAN TENTANG RAMBU LALU LINTAS DAN KETERAMPILAN BERBICARA SISWA KELAS III DALAM PEMBELAJARAN BAHASA INDONESIA - Qolbin, Albu; Muktadir, Abdul; Koto, Irwan (Jurnal Kajian Pendidikan Dasar, 2025)
This study aims to determine the effect of using flash card media on the knowledge of traffic signs and speaking skills of third grade students at SD Negeri 54 Lubuklinggau. This study used two classes, namely class IIIA with 20 students as an experimental class using flash card media and IIIB with 20 students as a control class without using flash card media. This type of research is Quasi Experiment with a quantitative approach. Data collection techniques use test questions and presentations explaining the contents of traffic sign cards and documentation to obtain school data information. The results of the hypothesis test research conducted on the experimental class and control class, from the results of the median rank of the experimental class (80.00) > the median rank score of the control class (72.50) for knowledge of traffic signs, while the results of the median rank of the experimental class (3.00) > the median rank score of the control class (2.25) for speaking skills, so it can be said that the use of flash card media has a statistically significant effect on the mastery of traffic sign knowledge and speaking skills of experimental class students (class IIIA).